SOSIALISASI DAN PEMETAAN POTENSI TANAH LONGSOR MENGGUNAKAN METODE MIKROSEISMIK DAN GEOLISTRIK DI KAWASAN OBJEK WISATA BUKIT NOBITA - Marzuki Marzuki; Mutya Vonnisa; Ahmad Fauzi Pohan; Arif Budiman; Imam Taufiq; Trengginas Eka Putra Sutantyo; Elistia Liza Namigo; Dian Milvita; Alimin Mahyudin; Nini Firmawati; Muldarisnur Muldarisnur; Afdal Afdal; Dahyunir Dahlan; M. Ali Shafii; Afdhal Muttaqin; Rico Adrial; Dedi Mardiansyah; Harmadi Harmadi; Zulfi Zulfi; Geby Sri Ayu Oktavia; Fani Anjelina; Nurul Annisa (LPPM Universitas Andalas, 2023)
Nobita Hill is one of the areas being developed as a tourist attraction in the city of Padang. Above Nobita Hill is a beautiful view, and you can see the picture of Padang City. However, the hilly topography with steep slopes makes this area prone to landslides. This activity aims to map the potential for landslides on Novita Hill. Activities start from preparation, implementation in the field, and evaluation. Field activities are carried out in two stages. The first stage is an experiment to map the landslide potential. The second stage is socialization. The target audience for this activity is the Village Head of Jua Nan XX Village and its officials and the community around Nobita Hill. The results of the study and mapping were disseminated to the village administration and community leaders involved in the development of the Bukit Nobita tourism area, which was carried out on November 16, 2022. The result of tourist objects often changes land use and cover. However, mitigation of the potential for landslides in this area has never been done. Therefore, the Andalas University Physics Department team mapped the potential for landslides on Novita Hill for six months, using microseismic and geoelectric methods. This activity obtained a map of the distribution of dominant frequencies, a map of the distribution of amplification, and an identification of slip planes concerning the potential for landslides on Nobita Hill. Furthermore, the results of the mapping and mitigation efforts have been disseminated to the village administration and community leaders involved in the development of the Bukit Nobita tourism area. This activity was carried out well. The landslide potential distribution map obtained from this activity is input for the community and stakeholders in developing the Buki Nobita tourist attraction that is safe from disasters.